Clinical Characteristics, Quality of Life, and Risk Factors of Amputation Stump Skin Disease and Stump Fungal Infection in Adult Amputees in Shanghai, China - Li, Yanqiao; He, Longwen; Lu, Xiangting; Du, Qian; Yu, Shijun; Huang, Xin (Frontiers in Microbiology, 2022)
Introduction: The stump site of amputees is clinically vulnerable and prone to various skin diseases. Data regarding the impact on quality of life (QoL) of amputees with amputation stump skin disease (ASSD) and risk factors of ASSD and stump fungal infection in the Shanghai area are yet unknown. Aims: This study aims to evaluate the QoL of amputees with ASSD and explore the risk factors of ASSD and stump fungal infection in the Shanghai area. Methodology: A total of 104 amputees from Shanghai Hebin Rehabilitation Hospital, Otto Bock (China) Industries Co. Ltd., Shanghai Tongji Hospital, and Shanghai Rehabilitation and Vocational Training Center for the Disabled were enrolled in this study. We collected demographic, clinical, and skin fungal examination data from these amputees from April 2015 to May 2021. Dermatology life quality index (DLQI) questionnaire was used to evaluate the QoL. The risk factors for ASSD and fungal skin infection were analyzed by the univariate analyses. Results: The median age of the 104 amputees was 57.9±11.9 years with an average amputation time of 17.7±15.1 years, and 73% of cases were men. The mean DLQI score of amputees with ASSD was 13.6, suggesting the severe impairment of QoL. Among amputees, 41 (39.4%) had confirmed ASSD, of whom 24 (58.5%) suffered from fungal skin infection, and the remaining were subjected to intertriginous dermatitis and eczema (22%), cutaneous keratosis (12.2%), and others (7.3%). Aspergillus (50%) was the most common species. The other fungal organisms included Trichophyton rubrum (33.3%), Candida krusei (8.3%), T. mentagrophytes (4.2%), and C. albicans (4.2%). ASSD rather than non-ASSD was more common in men (80.4%) and summer (46.3%). Summer (OR=3.31, 95% CI=1.19–9.17) was an established risk factor for ASSD compared to spring. The daily prosthesis wearing time >8 h was associated with stump fungal infection. Conclusion: The QoL of amputees with ASSD was severely affected, and the ASSD was characterized by fungal infection (tinea), intertriginous dermatitis, eczema, and skin keratosis. Summer and daily prosthesis wearing >8 h was a risk factor for ASSD. Aspergillus was the most common fungal species, especially when the stump was exposed in summer.